Emergence of the mcr-1 colistin resistance gene in extended-spectrum β-lactamase-producing Klebsiella pneumoniae in Taiwan. (March 2021) - Lin, Yu-Chi; Kuroda, Makoto; Suzuki, Satowa; Mu, Jung-Jung
Highlights: Analysis of mcr-1 -carrying plasmids in extended-spectrum β-lactamase-producing Klebsiella pneumoniae . An mcr-1 -carrying plasmid from human is highly similar to a plasmid from pig. IS Apl1 plays a pivotal role in the mobilisation of mcr-1 . Abstract: Objectives: The resistance of mcr-1 -carrying Enterobacteriaceae to polymyxins, which are last-resort antibiotics, has raised great concern worldwide. In this study, four mcr-1 -carrying plasmids isolated from Klebsiella pneumoniae clinical isolates were completely sequenced and the genome composition of the mcr-1 -carrying plasmids was analysed. Methods: Antimicrobial resistance genes and antimicrobial susceptibility of four mcr-1 -carrying K. pneumoniae isolates were characterised. Comparison of mcr-1 -carrying plasmids with closely related plasmids and analysis of the mcr-1 gene cassette were performed. Results: The genome composition of the four mcr-1 -carrying plasmids revealed the Tn 6330 and Tn 6390 cassettes embedded in two IncHI1-type plasmids, ΔTn 6330 in an IncHI2-type plasmid, and mcr-1 – pap2 in an IncX4-type plasmid. We also predicted the intermediate structures of the Tn 6330 and Tn 6390 cassettes. Conclusion: Dissemination of the colistin resistant gene mcr-1 in Taiwan could have been driven by various plasmids and mobile gene cassettes. Evolution of the genetic environment has led to diversity in the mcr-1 gene among plasmids. This work sheds light on the urgent need for continued surveillance of the worldwide distribution of mcr-1 and evaluates the public-health risk of colistin resistance.